Requirements Analysis for an Integrated OCL Development Environment - Chimiak-Opoka, Joanna; Demuth, Birgit; Silingas, Darius; Rouquette, Nicolas (Electronic Communications of the EASST, 2010)
An Integrated OCL Development Environment (IDE4OCL) can significantly improve the pragmatics and praxis of OCL. We present the domain concepts, toolâlevel interactions with OCL and the use cases we identified in a systematic analysis of requirements for an IDE4OCL. The domain concepts is an important contribution of our work as it attempts to clarify inconsistencies in the relevant specifications. Because OCL is not a standâalone language, the OCL landscape includes several interacting tools including an IDE4OCL. The use cases describe our vision of the desired functionality unique to an IDE4OCL. The results of our analysis and the long term vision of our work should be relevant to developers of OCL tools as well as to the OMG Request for Information regarding the UML Futures1. Our work is relevant to the UML Futures Roadmap because providing OCL for the constraints in the UML specification has been a longstanding problem at the OMG.